2017
DOI: 10.1111/ene.13223
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory profile discriminates clinical subtypes in LRRK2‐associated Parkinson's disease

Abstract: Inflammation seems to be associated with the presence of a specific clinical subtype in PD that is characterized by a broad and more severely affected spectrum of motor and non-motor symptoms. The pro-inflammatory metabolites IL-8, MCP-1 and MIP-1-β as well as BDNF are interesting candidates to be included in biomarker panels that aim to differentiate subtypes in PD and predict progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 40 publications
(51 reference statements)
1
41
0
Order By: Relevance
“…As serum IL-8 was stable across the day in the majority of PD individuals, this factor may be of interest in future longitudinal studies to determine whether it is associated with disease severity irrespective of disease duration or time of day. Consistent with this idea, the association of IL-8 with clinical severity was also reported in a recent analysis of human serum in a multi-center cohort of 142 subjects with familial PD arising from leucine rich repeat kinase 2 (LRRK2) mutations where high levels of IL-8, MCP-1, and CCL4 were associated with the presence of a specific clinical subtype that is characterized by a broad and more severely affected spectrum of motor and non-motor symptoms [ 89 ]. With regards to inflammatory markers in the CSF, IFNγ levels were higher in PD individuals with higher UPDRS total scores, higher activities of daily living (ADL) scores, and in PD individuals that have more complications from therapeutic treatment, suggesting that IFNγ levels may be of particular interest in disease staging and monitoring.…”
Section: Discussionmentioning
confidence: 81%
“…As serum IL-8 was stable across the day in the majority of PD individuals, this factor may be of interest in future longitudinal studies to determine whether it is associated with disease severity irrespective of disease duration or time of day. Consistent with this idea, the association of IL-8 with clinical severity was also reported in a recent analysis of human serum in a multi-center cohort of 142 subjects with familial PD arising from leucine rich repeat kinase 2 (LRRK2) mutations where high levels of IL-8, MCP-1, and CCL4 were associated with the presence of a specific clinical subtype that is characterized by a broad and more severely affected spectrum of motor and non-motor symptoms [ 89 ]. With regards to inflammatory markers in the CSF, IFNγ levels were higher in PD individuals with higher UPDRS total scores, higher activities of daily living (ADL) scores, and in PD individuals that have more complications from therapeutic treatment, suggesting that IFNγ levels may be of particular interest in disease staging and monitoring.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, no single inflammatory marker represents an ideal PD biomarker, but rather combinations of them or combinations with neuronal‐related biomarkers will most likely give a better opportunity to help in future patient selection, diagnosis, and prognosis. Specifically, biomarker panels using cytokines/chemokines (Brockmann et al., ) or combining neuronal and inflammatory markers (Delgado‐Alvarado et al., ; Eidson et al., ) are being proposed by us an others, as valuable tools to stage disease and potentially to distinguish clinical subtypes, and to monitor disease progression. For example, chemokines IL‐8, CCL2 (MCP‐1) and CCL‐4 (MIP‐1B), and the brain derived neurotrophic factor (BDNF), seem to be good markers to discriminate subtypes in PD‐LRRK2 patients because these markers are highest in patients with diffuse/malignant PD as compared to those with mainly pure motor disease.…”
Section: Soluble Immune Biomarkers May Help Stage Disease and Correlamentioning
confidence: 99%
“…For example, chemokines IL‐8, CCL2 (MCP‐1) and CCL‐4 (MIP‐1B), and the brain derived neurotrophic factor (BDNF), seem to be good markers to discriminate subtypes in PD‐LRRK2 patients because these markers are highest in patients with diffuse/malignant PD as compared to those with mainly pure motor disease. (Brockmann et al., ). These immune markers, IL‐8, CCL2, CCL4, were also correlated with more severe motor defects PD (Reale et al., ), and they were also higher in glucocerebrosidase (GBA)‐PD (Chahine et al., ).…”
Section: Soluble Immune Biomarkers May Help Stage Disease and Correlamentioning
confidence: 99%
“…The world‐wide prevalence of Parkinson disease (PD) is rising steadily as the global population ages and significant advances are being made in the understanding of pathogenesis and treatment . It is of interest that in Portugal, where there is a high prevalence of LRRK2 G2019S mutation in PD, a recent study found PD prevalence to be 0.24% of those aged >50 years, with a total of 180/100 000 population, rather lower than might be expected, although this is probably explained by methodological issues .…”
mentioning
confidence: 99%
“…It is of interest that in Portugal, where there is a high prevalence of LRRK2 G2019S mutation in PD, a recent study found PD prevalence to be 0.24% of those aged >50 years, with a total of 180/100 000 population, rather lower than might be expected, although this is probably explained by methodological issues . This mutation may be associated with specific inflammatory markers that appear to be associated with the severity of motor and non‐motor dysfunction, and these could provide a useful biomarker for stratification . A similar suggestion is that the presence of rapid eye movement sleep behaviour disorder may also be associated with specific patterns of motor function and striatal dopamine transporter uptake .…”
mentioning
confidence: 99%